Perancangan Motion Graphic Iklan Layanan Masyarakat tentang Edukasi Bahaya Obesitas pada Anak di Malang - Titi Ayu Pawestri; Purwati Endah Darmayanti (Jurnal VOK@SINDO, 2017)
Obesity is a common problem that children experience. Obesity is a disorder or disease that is characterized by overfunding body fat. The pattern of lifestyle is less active and dietary errors make a lot of fat buried in body fat tissue. Obesity has many negative impacts to its sufferers, both psychological impact and physical health of children. Such as the bullying treatment of his friends that can cause the child to become inferior even can also cause diseases such as diabetes, high blood, even death. Children generally still lay with the dangers of obesity for that required more media in the minds of people, especially children. So children can change lifestyles to be healthier. Public service advertisement becomes an alternative socialization for education of obesity hazard. This advertisement is packed using motion graphic animation. The animation of motion graphic in Public Service Advertisement is displayed in the form of two-dimensional animation (2D).